1982
DOI: 10.1093/ajcn/36.6.1205
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in North American women. I. Effects of diet, cigarette smoking, and psychological stress on maternal weight gain

Abstract: This study examined the roles of diet, cigarette smoking, and psychological stress in pregnancy weight gain. The 60 were selected by defined criteria to minimize variation in anthropometric, socioeconomic, and medical variables which also affect weight gain. To maximize variation in weight gain, subjects were also selected on the basis of low weight gain (less than or equal to 15 lb) and adequate weight gain (greater than 15 lb). Each weight gain group contained smokers and nonsmokers. Smokers consumed more ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 35 publications
2
28
0
3
Order By: Relevance
“…As in previous studies, 17,19 our study showed that energy intake, independent of BMI status, was related to net weight gain. The single study that did not ®nd a signi®cant association between energy intake and weight gain used a less precise dietary assessment method (one 48 h recall obtained during a structured telephone interview).…”
Section: Discussionsupporting
confidence: 88%
“…As in previous studies, 17,19 our study showed that energy intake, independent of BMI status, was related to net weight gain. The single study that did not ®nd a signi®cant association between energy intake and weight gain used a less precise dietary assessment method (one 48 h recall obtained during a structured telephone interview).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the notion that birth outcomes are affected both by biomedical and by psychosocial factors, medical risk and parity (whether or not a woman has given birth previously) are two of the most important biomedical predictors of birth outcome (Binsacca et al, 1987;Buescher et al, 1988;Cramer, 1987;Dott and Fort, 1975;Institute of Medicine, 1985;Shiono et al, 1986) and should therefore be controlled when examining the impact of prenatal stress on birth outcome. Some studies have used samples homogeneous in medical risk and parity to control for the effects of these characteristics (e.g., Bradley, 1983;Lederman et al, 1979;Levi et al, 1989;Picone et al, 1982). However, the results of such studies may not be generalizable to populations of different risk level or parity.…”
Section: Control For Medical Risk and Paritymentioning
confidence: 99%
“…Several studies report no association with gestational age (Molfese et al, 1987a;Picone et al, 1982) or preterm delivery (Ching and Newton, 1982;Larsson et aL, 1987;Williams et al, 1975), with birth weight (Ching and Newton, 1982;Larsson et al, 1987;Picone et al, 1982), or with neonatal morbidity (Ching and Newton, 1982;Larsson et aL, 1987). The best conducted study of objectively weighted life event stress, with a point value of 5, finds that it has no significant effects (Picone et al).…”
Section: Objective Life Event Weightsmentioning
confidence: 99%
“…Cigarette use stimulates the vigil system and therefore increases the levels of catecholamines and ACTH [46] In addition, increases the levels of catecholamines for at least 30 minutes. Therefore, the regular habit of smoking, decreases uterine blood flow [47].…”
Section: Stress Factors Of Pregnant Womenmentioning
confidence: 99%